The role of the Africentric worldview in the Liberatory process - Hill, Brian J. (Frontiers in Sociology, 2023)
The Black Lives Matter movement brings increasing awareness to systemic racism in American society; nonetheless, the Eurocentric worldview and intellectual racism remain prevalent. Students in adult education graduate courses have little opportunity to engage with the significant base of Africentric knowledge. When such opportunities do arise, however, they are powerful and transformative. This paper conducts a case study of four students of African descent enrolled in graduate programs that engaged with Africentric knowledge. The results demonstrate that such experiences can create a powerful Liberatory transformation. This Liberatory process is laid out in five steps along with a discussion of the implications for practice and research.